Challenges and opportunities of genetic improvement in alpacas and llamas in Peru - Gutierrez, G. (2018)
Alpacas and llamas play an important role in the livelihood of many rural families in the High Andes of Peru. The census of 2012 indicates a population of 3 million alpacas and 746,269 llamas. Both species are kept in extensive, low-input, pasture-based systems in altitudes between 3800 m and up to 5000 meters above sea level. Smallholders keep mixed herds of sheep, alpaca and llamas as a mitigation strategy against fluctuating market prices. Since 1997 the Peruvian Ministry of Agriculture manages a genealogy registry for alpacas and llamas, but so far the up-take rate by farmers and inscription rate of animals is low. The national research organisation INIA (Instituto Nacional de Innovación Agaria) runs an ex-situ in-vivo conservation program for coloured alpacas (21 different colours) and llamas. INIA is also doing research in the area of embryo transfer, artificial insemination and controlled mating. There is no national breeding program for alpacas, but all individual initiatives from private companies, NGOs and farmers´ cooperatives aim to improve fibre quality by reducing fibre diameter. At the moment these various local programs are not connected. There is also no national breeding program in place for llamas. Little attempts have been made to set up functional breeding programs for this species. Furthermore, there is no a national conservation plan in place. However, INIA have just started the formulation phase of a National Bank for Agrobiodiversity Conservation that include ex situ in vitro conservation of SACs. The Peruvian Ministry of agriculture prioritizes in the recently launched national livestock development plan for 2017 – 2027 alpacas and llamas. Support for the development of breeding plans is mentioned as one action line to increase productivity in both species.